2004
DOI: 10.1111/j.0818-9641.2004.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the immunocompetent cells that bind early pregnancy factor and preliminary studies of the early pregnancy factor target molecule

Abstract: Summary Early pregnancy factor (EPF) is a secreted protein with immunosuppressive and growth factor properties. It has been shown to suppress the delayed-type hypersensitivity response in mice as well as acute and chronic forms of experimental autoimmune encephalomyelitis in rats and mice, respectively. In previous studies, we have demonstrated that EPF binds to a population of lymphocytes and we hypothesized that it mediates its suppressive effects by binding to CD4 + T cells. In the present study, we isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 45 publications
1
19
0
1
Order By: Relevance
“…This line of reasoning might lead one to speculate that the physiological role of circulating Hsp10 during early pregnancy (38) may be to remove the Hsp60 danger signal (15) that has arisen from pregnancy (73,74) rather than from pathogen-induced tissue damage. We are currently in the process of seeking formal proof of Hsp10 binding to extracellular Hsp60, as it remains possible that Hsp10 binds to an alternative receptor (75) and that Hsp10 and anti-Hsp60 exert similar suppressive (but non-additive) effects on TLR4 signaling (Fig. 7) but use distinct pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This line of reasoning might lead one to speculate that the physiological role of circulating Hsp10 during early pregnancy (38) may be to remove the Hsp60 danger signal (15) that has arisen from pregnancy (73,74) rather than from pathogen-induced tissue damage. We are currently in the process of seeking formal proof of Hsp10 binding to extracellular Hsp60, as it remains possible that Hsp10 binds to an alternative receptor (75) and that Hsp10 and anti-Hsp60 exert similar suppressive (but non-additive) effects on TLR4 signaling (Fig. 7) but use distinct pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In a human model, it has been shown that EPF binds specifically to CD4 ϩ , CD8 ϩ , CD14 ϩ (monocytes), and CD56 ϩ natural killer cells, and its suppressive effects are driven by inhibition of CD4 ϩ T cell activity (Athanasas-Platsis et al 2004). At the same time, EPF is known to stimulate the proliferation of many different cells .…”
Section: Many Faces Of Hsp10mentioning
confidence: 99%
“…It is known that TLR 4 is needed for lps induced injury of oligodendrocytes (Lehnardt et al 2002), and it may be that cpn 10 supports the survival of oligodendrocyte precursors in vitro through a mechanism involving toll-like receptors. However, there is also some evidence that there may be a specific receptor for EPF/cpn 10 (Athanasas- Platsis et al 2004), which provides another possible mode of action. The suggestion of an extracellular role for heat-shock proteins (hsps) such as cpn 10 is not unprecedented.…”
Section: Discussionmentioning
confidence: 99%